Over-Expression of Long Non-Coding RNA-AC099850.3 Correlates With Tumor Progression and Poor Prognosis in Lung Adenocarcinoma - Chen, Xi; Guo, Jishu; Zhou, Fan; Ren, Wenjun; Pu, Jun; Mutti, Luciano; Niu, Xiaoqun; Jiang, Xiulin (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) is the most common histological lung cancer, and it is the leading cause of cancer-related deaths worldwide. Long noncoding RNAs (lncRNAs) have been implicated in the initiation and progression of various cancer. LncRNA-AC099850.3 is a novel lncRNA that is abnormally expressed in diverse cancer types including LUAD. However, the clinical significance, prognostic value, diagnostic value, immune role, and the potential biological function of AC099850.3 LUAD remains elusive. In this study, we found that AC099850.3 was highly expressed in LUAD and associated with advanced tumor stage, poor prognosis, and immune infiltration. Receiver operating curve analysis revealed the significant diagnostic ability of AC099850.3 (AUC=0.888). Functionally, knockdown of AC099850.3 restrained LUAD cell proliferation and migration in vitro. Finally, we constructed a ceRNA network that included hsa-miR-101-3p and 4 mRNAs (ESPL1, AURKB, BUB3, and FAM83D) specific to AC099850.3 in LUAD. Kaplan-Meier survival analysis showed that lower expression of miR-101-3p, higher expression of ESPL1, AURKB, BUB3, and FAM83D, were associated with adverse clinical outcomes in patients with LUAD. This finding provided a comprehensive view of the AC099850.3-mediated ceRNA network in LUAD, thereby highlighting its potential role in diagnosis and prognosis of LUAD.